Enhanced collaboration of physicians and speech-language therapists promotes early oral intake in older adults with aspiration pneumonia: A retrospective cohort study - Akinori Tawaraya; Atsushi Keyaki (PLoS ONE, 2026)
Background & aims Early swallowing assessment and initiation of oral intake are important in the management of aspiration pneumonia in older adults. However, the factors influencing early initiation of oral intake have not been widely studied. We implemented a system of enhanced collaboration between physicians and speech-language therapists (ECPS) as a structured inter-professional clinical pathway to standardize decision-making and facilitate early oral intake. We hypothesized that ECPS would increase the rate of early oral intake within two days of admission. Methods This retrospective cohort study included inpatients aged ≥65 years with aspiration pneumonia (ECPS and control groups). Multivariate logistic regression was used to evaluate the associations of ECPS with early oral intake. Secondary outcomes assessed safety in an exploratory analysis, examining whether early oral intake was associated with disadvantages such as longer duration of antibiotic therapy, recurrence of aspiration pneumonia, decline in swallowing function, need for artificial nutrition, change in residence, or longer hospital stay. Results The ECPS group comprised 160 of the 300 eligible patients. ECPS was associated with increased odds of early oral intake success (OR = 3.85, 95% CI: 2.22–6.70, p < 0.001). Furthermore, delayed swallowing assessment was associated with decreased odds of early oral intake success (OR = 0.69, 95% CI: 0.53–0.90, p < 0.01). In exploratory analysis, early oral intake was not associated with any clear increase in disadvantages. Conclusion Structured collaboration between physicians and swallowing specialists regarding early oral intake could represent a factor worth considering in achieving effective management in older adults with aspiration pneumonia.